Kesalahan Siswa MTs dalam Menyelesaikan Soal KSM Matematika Integrasi dengan Menerapkan Teori Polya Ditinjau dari Kemampuan Koneksi Matematis - primrose, ailsa tsabita; Nur Falah, Muhammad Faiz; Masamah, Ulfa (Galois: Jurnal Penelitian Pendidikan Matematika, 2024)
ABSTRACT This study aims to (1) identify student errors in solving KSM Mathematics Integration questions in terms of mathematical connection skills (2) identify student error factors in solving KSM mathematics integration questions in terms of mathematical connection skills. The research approach used is qualitative with descriptive type. The data collection technique used a test in the form of KSM mathematics integration questions at the City/Cab level and structured interviews. The research subjects were 3 8th grade Olympic and 9th grade Olympic students who had participated and passed the KSM at the City/Cab level and had high mathematical connection skills. The sampling technique used purposive sampling. The data analysis technique uses Milles and Huberman which includes data reduction, data presentation, and conclusion drawing. The results of this study indicate the existence of student errors by applying Polya's theory in solving KSM mathematics integration problems which include (1) errors in receiving information including student errors in writing what is known and student errors in determining what is asked, (2) errors in algebraic concepts, namely linear equations of one variable, (3) errors in computation, and (4) errors in understanding the concepts of Thawaf and Sa'i. With these findings, the study recommends teachers use learning strategies that can improve students' mathematical connection skills, such as the use of appropriate learning models. The conclusion of this study can be a guide for educators and researchers in developing effective learning methods to overcome student errors in the context of KSM Mathematics Integration.